Uncovering the dual roles of peripheral immune cells and their connections to brain cells in stroke and post-stroke stages through single-cell sequencing - Xu, Zheng; Yang, Fan; Zheng, Lifang (Frontiers in Neuroscience, 2024)
Ischemic stroke is a cerebrovascular disease that affects the blood vessels and the blood supply to the brain, making it the second leading cause of death worldwide. Studies suggest that immune cells play a dual role during the inflammatory and recovery phases of stroke. However, in-depth investigations of specific cell subtypes and their differentiation trajectories remain to be elucidated. In this review, we highlight the application of single-cell RNA sequencing (scRNA-seq) for the unbiased identification of cell heterogeneity in brain and peripheral blood mononuclear cells (PBMCs) during and after a stroke. Our goal is to explore the phenotypic landscape of cells with different roles in this context. Specifically, we provide an overview of the roles, cell surface markers, immune cell-released cytokines, and intercellular interactions identified in major immune cells during and after stroke, as identified by different technologies. Additionally, we summarize the connection between immune cells in peripheral blood and the brain via their differentiation trajectories. By synthesizing the application of scRNA-seq in the combined analysis of PBMCs and brain tissue at higher sampling frequencies, we aim to unveil the dual role of peripheral immune cells, which could facilitate the development of new treatment strategies for ischemic stroke.